A STUDY OF DEVELOPMENT TRENDS IN ROHTAK CITY (INDIA) WITH REFERENCE TO NCR (NATIONAL CAPITAL REGION) POLICIES FOR HARYANA SUB-REGION - Nagpal, Aarti (MATTER: International Journal of Science and Technology, 2017)
Rohtak is a regional center of NCR (National Capital Region). The main emphasis of the N.C.R. plan has been the economic development of the identified regional centres. The city of Rohtak has been the centre of political, educational and cultural activities in Haryana. Rohtak has become major educational centre of Haryana during the last two decades. Apart from being part of NCR, Rohtak is now experiencing rapid urbanization and industrial development in its trunk routes. National Capital Region is a result of Regional planning efforts to ensure planned growth of National capital and surrounding settlements. The NCR concept, was evolved with objectives of decongesting the National Capital and planned development of Delhi and the surrounding region through dispersal of economic, commercial and industrial activities in DMA and priority towns or Regional centers within the NCR and the counter-magnets identified outside the NCR territory. Development trends reveal that Rohtak is developing fast towards North-East and South-East. With the induced economic momentum in Rohtak city mass employment would be possible and it’ll arrest the migration to National Capital. This ultimately will fulfill the aim of NCRPB to decongest the NCT (Delhi) by decentralization.